POLAND’S NATIONAL SECURITY POLICY IN A NEW REGIONAL SECURITY ENVIRONMENT. CASE STUDY: NATIONAL SECURITY STRATEGY OF POLAND (2014) - Moldovan, Anton (Torun International Studies, 2018)
Military aggression launched by Russia against Ukraine was a turning point on the international arena; and particularly in Europe. The Russian aggression against Ukraine, concluded by the illegal occupation and annexation of the Crimean Peninsula represented the first postCold War event in which one state claimed – equipped with the full array of force – a territory belonging to another state, whose borders are recognised under the international law. Russian aggression triggered a general concern in Eastern Europe. The Polish leaders were among the first European officials who vehemently condemned the actions taken by Russia. This paper aims to explore Polish stance on Russian military aggression against Ukraine and how the Polish leadership posture is reflected in the new concept of the national security strategy. Thus, we focus on the National Security Strategy of Republic of Poland (2014). The case study is structured on two levels of analysis that help us understand the context in which Polish national security strategies and policies have been formulated throughout last years. On the one hand, national security strategies and foreign policy priorities have been formulated in accordance with the status of membership within North Atlantic Alliance (and the European Union). On the other hand, the sense of insecurity originating from its eastern borders and particularly negative historical experiences and tense relations with the Russian Federation under the Putin regime have been taken into consideration in the formulation of national security strategies and Policie.